2007
DOI: 10.1530/eje-06-0707
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent changes in the expression of thyroid hormone receptor α1 in the myocardium after acute myocardial infarction: possible implications in cardiac remodelling

Abstract: The present study investigated whether changes in thyroid hormone (TH) signalling can occur after acute myocardial infarction (AMI) with possible physiological consequences on myocardial performance. TH may regulate several genes encoding important structural and regulatory proteins particularly through the TRa1 receptor which is predominant in the myocardium. AMI was induced in rats by ligating the left coronary artery while sham-operated animals served as controls. This resulted in impaired cardiac function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
(43 reference statements)
1
27
0
3
Order By: Relevance
“…However, it is now recognized that low total T 3 levels in plasma may be an independent factor for mortality in patients with heart failure (5,6), indicating that thyroid hormone probably has an important role in the pathophysiology of heart failure. Such a possibility is further supported by recent experimental studies which clearly demonstrate that changes in thyroid hormone-thyroid nuclear receptor axis occur in the failing myocardium and correlate to cardiac dysfunction (7)(8)(9)(10). Based on this evidence, the present study has further explored whether thyroid hormone can be correlated to functional myocardial status in patients with dilated cardiomyopathy of ischemic or non-ischemic origin.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, it is now recognized that low total T 3 levels in plasma may be an independent factor for mortality in patients with heart failure (5,6), indicating that thyroid hormone probably has an important role in the pathophysiology of heart failure. Such a possibility is further supported by recent experimental studies which clearly demonstrate that changes in thyroid hormone-thyroid nuclear receptor axis occur in the failing myocardium and correlate to cardiac dysfunction (7)(8)(9)(10). Based on this evidence, the present study has further explored whether thyroid hormone can be correlated to functional myocardial status in patients with dilated cardiomyopathy of ischemic or non-ischemic origin.…”
Section: Introductionsupporting
confidence: 53%
“…There is accumulating experimental evidence showing that changes in thyroid hormone and/or thyroid hormone receptors (TRs) can occur in cardiac hypertrophy and myocardial infarction, and this seems to be of physiological relevance (7)(8)(9)(10). More importantly, after myocardial infarction in rats, changes in myosin isoform expression in the myocardium are evident, corresponding to exacerbation of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is modulated by TH reshaping LV chamber toward a more ellipsoidal shape. The above mentioned responses seem to involve distinct signaling pathways, comprising: low TH levels, increased D3 activity, increased expression of thyroid receptor protein α1 (TRα1) and decreased TR β1 protein expression in the myocardium [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the degree of thyroid dysfunction was associated with severity of diseases, and low levels of biologically active TH predicted poor prognosis in several diseases (26)(27)(28)(29)(30). Previous studies have reported that low total T 3 levels were associated with increased mortality and impaired cardiac function and were strong prognostic predictors of death in heart disease (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%